2004
DOI: 10.1104/pp.104.045369
|View full text |Cite
|
Sign up to set email alerts
|

Patellin1, a Novel Sec14-Like Protein, Localizes to the Cell Plate and Binds Phosphoinositides

Abstract: Membrane trafficking is central to construction of the cell plate during plant cytokinesis. Consequently, a detailed understanding of the process depends on the characterization of molecules that function in the formation, transport, targeting, and fusion of membrane vesicles to the developing plate, as well as those that participate in its consolidation and maturation into a fully functional partition. Here we report the initial biochemical and functional characterization of patellin1 (PATL1), a novel cell-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
162
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(179 citation statements)
references
References 139 publications
15
162
0
2
Order By: Relevance
“…PATL1 has been localized to the cell plate in dividing cells but also associates with PLASMODESMATA-LOCATED PROTEIN1 (PDLP1) during downy mildew infection and may colocalize with PDLP1 at the extrahaustorial membrane (Caillaud et al, 2014). We confirmed the presence of both PATL1 and PATL2 in the P40 fraction using anti-PATL antibodies (Peterman et al, 2004;Deng et al, 2007; Fig. 6A; Supplemental Fig.…”
Section: Protein Content Of Plant Evssupporting
confidence: 65%
See 1 more Smart Citation
“…PATL1 has been localized to the cell plate in dividing cells but also associates with PLASMODESMATA-LOCATED PROTEIN1 (PDLP1) during downy mildew infection and may colocalize with PDLP1 at the extrahaustorial membrane (Caillaud et al, 2014). We confirmed the presence of both PATL1 and PATL2 in the P40 fraction using anti-PATL antibodies (Peterman et al, 2004;Deng et al, 2007; Fig. 6A; Supplemental Fig.…”
Section: Protein Content Of Plant Evssupporting
confidence: 65%
“…Membranes were washed with 13 Tris-buffered saline (50 mM Tris-Cl and 150 mM NaCl, pH 7.5) containing 0.1% Tween 20 (TBST) and blocked with 5% Difco Skim Milk (BD) overnight at 4°C. Membranes were incubated with monoclonal mouse anti-GFP or anti-mCherry antibody (Abcam) at a 1:3,000 dilution or polyclonal anti-PATL1 (Peterman et al, 2004;Deng et al, 2007) at a 1:5,000 dilution for 1 h, washed with TBST, and incubated with horseradish peroxidase-labeled goat anti-mouse or anti-rabbit antibody (Abcam) at a 1:5,000 dilution for 1 h. After a final wash in TBST, protein bands were imaged using Immuno-Star Reagents (Bio-Rad) or Supersignal West Femto Maximum Sensitivity Substrates (Thermo Scientific) and x-ray film. Band intensities were quantified using the FlourChem E system with AlphaView SA software (version 3.4.0; ProteinSimple).…”
Section: Immunoblotsmentioning
confidence: 99%
“…Phosphorylated patellin-1 (spot 22) also showed a 7-fold up-regulation. This protein belongs to a small family of Sec14 and GOLD domains-containing lipidbinding proteins probably involved in membrane-trafficking events [44]; phosphoproteomic studies on membrane fractions of salt-stressed Arabidopsis demonstrated that patellin-2 phosphorylation levels raise upon stress [28]. Phosphorylated fibrillin-3 (spot 29) also showed increased levels.…”
Section: Chitosan Treatmentmentioning
confidence: 99%
“…We found here that MtAnn2 also is strongly, but transiently, up-regulated 4 h after NF treatment in epidermal cells (Table II). Two small GTPase Ras-related proteins, potentially involved in polarized membrane trafficking (Vernoud et al, 2003), and three patellins (Sec14 and GOLD domain proteins, also implicated in membrane trafficking; Peterman et al, 2004), were additionally identified as NF-induced genes. Arabidopsis (Arabidopsis thaliana) PATELLIN1 is thought to bind phosphatidylinositol and its phosphorylated derivatives, themselves known to regulate membrane trafficking (Peterman et al, 2004).…”
Section: Genes Encoding Proteins Involved In Cell Dynamicsmentioning
confidence: 99%